Analysis of New Student Information Sources in Determining College Choices - Nana Noviada Kwartawaty; Albertus Setyo Sumargo; Achmad Solechan (Institut of Shanti Bhuana, 2026)
This study aims to analyze the information sources used by new students in determining their college choices, identify the most dominant sources, and evaluate their effectiveness based on conversion rates from applicants to accepted students. Previous studies tend to examine the influence of individual channels such as social media, websites, or interpersonal factors separately, without integrating the dual dimensions of reach (awareness) and conversion (decision effectiveness). This limitation creates a gap in developing data-driven and strategically targeted higher education promotion models. This study employs a descriptive quantitative approach using secondary data from 4,028 applicants, of which 798 were accepted. Data were analyzed using frequency distributions, percentages, and conversion rate analysis across various information sources. The findings indicate a clear distinction between information sources that generate awareness and those that drive conversion. School promotions and guidance counselors dominate in terms of reach, while interpersonal sources (family and friends) and digital channels (WhatsApp, websites, and Instagram) demonstrate higher conversion effectiveness. The novelty of this study lies in its integrative approach that simultaneously evaluates reach and conversion across multiple information sources, offering a more comprehensive understanding of student decision-making. Practically, this study provides a data-driven foundation for designing integrated promotion strategies, where offline channels enhance awareness and digital as well as interpersonal channels optimize conversion outcomes.